2019
DOI: 10.1038/s41467-019-09164-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of APP with GABAB receptors links axonal trafficking to amyloidogenic processing

Abstract: GABAB receptors (GBRs) are key regulators of synaptic release but little is known about trafficking mechanisms that control their presynaptic abundance. We now show that sequence-related epitopes in APP, AJAP-1 and PIANP bind with nanomolar affinities to the N-terminal sushi-domain of presynaptic GBRs. Of the three interacting proteins, selectively the genetic loss of APP impaired GBR-mediated presynaptic inhibition and axonal GBR expression. Proteomic and functional analyses revealed that APP associates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(148 citation statements)
references
References 66 publications
(140 reference statements)
8
108
1
1
Order By: Relevance
“…Interestingly, Reelin interacts with APP [8,9,21]. GABA B R1, which functionally interacts with the APP ectodomain to regulate presynaptic inhibition [5,22] has strikingly high overlap with the relatively heterogenous population of APP-positive cells. 98% of APP-positive cells in CA1 are GABA B R1-positive ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Reelin interacts with APP [8,9,21]. GABA B R1, which functionally interacts with the APP ectodomain to regulate presynaptic inhibition [5,22] has strikingly high overlap with the relatively heterogenous population of APP-positive cells. 98% of APP-positive cells in CA1 are GABA B R1-positive ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined the co-expression of APP with γ-aminobutyric acid type B receptor subunit 1(GABA B R1) ( Fig. 1e), which functionally interacts with the APP ectodomain to regulate presynaptic inhibition [5,22] and is reported to label a neurochemically heterogeneous subset of interneurons [26]. All APP-positive cells at the SR/SLM border (100%) and in the SO (100%) are GABA B R1-positive ( Fig.…”
Section: App Is Prominently Expressed In a Subset Of Hippocampal Intementioning
confidence: 99%
“…A GBR antagonist disinhibits sAPP‐inhibited release, supporting that sAPP acts as GBR agonist or positive allosteric modulator. A related report shows that binding of full‐length APP to the N‐terminal sushi domain of GB1a is necessary for vesicular trafficking of GBRs to axon terminals . Consistent with vesicular GBR transport, kinesin‐1 adaptors of the c‐Jun N‐terminal kinase‐interacting protein (JIP) and calsyntenin (CSTN) protein families are shown to bind to APP and to link the APP/GBR complex to kinesin‐1 motors.…”
Section: Functions Of Non‐obligate Receptor Componentsmentioning
confidence: 81%
“…The two proteins are expected to localize to adherens junctions that mediate adhesion between pre‐ and post‐synaptic membranes . AJAP‐1 and PIANP do not play a role in vesicular axonal trafficking of GBRs . Possibly, these proteins anchor GB1a/2 receptors at synaptic sites by binding to the sushi domains in cis or in trans .…”
Section: Functions Of Non‐obligate Receptor Componentsmentioning
confidence: 99%
“…2E) also validated the increase of APP in SV2A de ciency situation. It has been well documented that APP is stabilized by the GABA B receptor, at the cell surface, which leads to a reduction in APP proteolysis to Aβ [44]. Meanwhile, it has also been demonstrated that SV2A de ciency impairs its interaction with synaptotagmin 1 causing a speci c disruption of synaptic GABA release, which in turns downregulates GABA B receptor expression [45].…”
Section: Discussionmentioning
confidence: 99%